The Impact of The Transition from Traditional Accounting to Cloud Accounting on The Accuracy of Financial Statements: A Field Study At Rafidain and Rashid Banks/Babylon Branch - Alfartoosi , Ali Mohammed huseein; Mohsin , Hussein Jaleel (International Journal of Accounting and Economics Studies, 2025)
The study aims to analyze the impact of the transition from traditional accounting to cloud accounting on the accuracy of financial statements in the banking sector through a field study conducted at the Rafidain and Rasheed Banks, the Babylon branch. The research focuses on evaluating the extent to which cloud-based accounting systems improve the quality of accounting information, reduce errors, and enhance processing efficiency compared to traditional systems. The researcher employed a descriptive-analytical approach, distributing a questionnaire to a sample of accountants and auditors at two banks. The collected data were analyzed using appropriate statistical tools to test the research hypotheses. The findings revealed a statistically significant positive relationship between the adoption of cloud accounting and the enhancement of financial statement accuracy. Cloud technology contributed to minimizing accounting errors, increasing data reliability and transparency, and improving the efficiency of financial operations. The study recommends accelerating the adoption of cloud accounting across other branches of Iraqi banks while ensuring the provision of necessary infrastructure and training for employees to maximize the benefits of this technology in enhancing the accuracy of financial reporting.